PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP TAX AVOIDANCE (Media Riset Akuntansi, 2022)
The purpose of this study was to determine and analyze the effect of good corporate governance on tax avoidance as proxied by cash effective tax rates in banking companies listed on the IDX. The independent variable in this study is the proportion of institutional ownership, independent board of commissioners, managerial ownership, audit committee and audit quality. The population of this study are banking companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2016. The sampling technique used was purposive sampling method, in order to obtain as many as 24 samples. This study uses a descriptive analysis method using the SPSS 23 program. The results show that institutional ownership, independent commissioners, and managerial ownership have no significant effect on tax avoidance. Meanwhile, the audit committee and audit quality have a significant effect on tax avoidance. The results of this study are expected to contribute to the field of financial accounting.